Wasilat fidyu alrusum al mutaharikat ‘abro CapCut ‘alā mahārāt al istima’ litulāb al safi al sābi’ fi al Madrasah al Tsānawiyah al islāmiah al hukūmiyat 3 lima Puluh Kota - Adrianti, Yudia (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2024)
The main problem in this research is "what is the influence of animated video media via CapCut in learning listening skills for class VII students at MTsN 3 Limapuluh Kota?”. The research objectives are as follows: To reveal the listening skills of class students VII at MTsN 3 Lima puluh Kota before using animated video media via CapCut, to reveal the use of animated video media via CapCut in listening skills for class students VII at MTsN 3 Lima puluh Kota, and to determine the effectiveness of CapCut animated video media on listening skills after being used for class students VII at MTsN 3 Lima puluh Kota. This research approach is quantitative. The research method that researchers use is an experimental method based on field research. The data collection techniques are interviews, tests and documentation. The results of the research are (1)after the researcher conducted a pre-test in the experimental class and control class, the students' ability in Arabic, especially listening skills without animated video media via CapCut, was weak. Because researchers found that the results of the pre-test listening skills were at the lowest level, (2)the use of animated video media via CapCut in Arabic in the listening skills of class students VII MTsN 3 Lima Puluh Kota From preliminary activities to final activities, educational and teaching activities using animated video media via CapCut were carried out "very well". (3)After the researchers conducted the experiment, the use of animated video media via CapCut in teaching listening skills was effective.